Practical implementation of blended learning in terms of English as a foreign language at technical universities; Ponte; Vol. 72, iss. 10 - Sumtsova O. V. Olga Vitalievna; Aikina T. Yu. Tatiana Yurievna; Zubkova O. M. Olga Mikhaylovna; Voronkova M. A. Mariya Aleksandrovna (2016, 2016)
Title screen